Effect of Ondansetron on Postoperative Pain and Vomiting after Acute Appendicitis Surgery: A Placebo-Controlled Double-Blinded Randomized Clinical Trial - Moein Khoori; Peyman Mirghaderi; Alireza Azarboo; Forough Jamil; Nasim Eshraghi; Alireza Abdollahzadeh Baghaei (Pain Research and Management)
Background. Common postoperative complications following surgery, particularly acute appendicitis surgery, include postoperative pain and vomiting, which can cause discomfort and delay recovery time. Methods. A randomized double-blinded placebo-controlled clinical trial was conducted with 80 cases of acute appendicitis of American Society of Anesthesiologists (ASA) physical status I or II and aged 18–60 y/o scheduled for appendectomy under general anesthesia. Patients were randomly divided into two equal groups: group A received 4 mg of ondansetron IV (2 ml) and group B received 2 ml of normal slain IV (placebo). Pain according to VAS, nausea and vomiting according to clinical symptoms, shivering and sedation according to the Bedside Shivering Assessment Scale (BSAS), and the Ramsay Sedation Scale (RSS) at 2, 6, 12, and 24 hours after surgery were evaluated and compared between the groups. Results. There was a significant decline in the severity of pain only at 2 hours after surgery between the ondansetron and control groups (5.3 ± 1.0 vs. 6.0 ± 1.0; p=0.01), not showing a difference between the groups at 6, 12, and 24 hours after appendectomy. Postoperative nausea and vomiting at 2 (5% vs. 25%; p=0.03) and 6 (7.5% vs. 27.5%; p=0.04) hours after appendectomy in the ondansetron group. At different times, the ondansetron and control groups did not differ in terms of pethidine consumption or sedation. Conclusions. In conclusion, our study found that ondansetron was effective in reducing postoperative vomiting after acute appendicitis surgery. However, it did not show a clinically significant effect on postoperative pain. This trial is registered with IRCT20230722058883N1.